Influence of the test emulsion on filtration efficiency and pressure drop of mist separators for cooling lubricants - Wilhelm Hoeflinger; Dunja Sokolović (Zaštita Materijala)
This work deals with standardized filter tests of mist separators for cooling lubricants aerosols. The Austrian standard ÖNORM Z1263 describes a filter test rig and test procedure for standardized comparable filter tests and futher for a classification. Following this guideline six industrial used filter elements with different designs and materials were tested to determine filtration specific parameters like the pressure drop, total liquid holdup, oil holdup and separation efficiency. Finally, filter elements will be classified by their separation efficiency into a filter-class from 1 to 10. The ÖNORM Z1263 does not give any specific test substance, so there is an interest to study the influence of various coolant oils as used in industry. Therefore for the filter test, three different coolant oils were used as test substance: mineral oil, semi-synthetic oil and full-synthetic oil. The six filter elements have been tested according to the guideline to reach a steady-state liquid equilibrium within 2-4 hours. Comparing the results of the steady-state pressure drop, total holdup and oil holdup as well as the separation efficiency in four particle size ranges there was no significant influence of the test oil base found. The achieved filter-class numbers differ only by one number.